The Effects of the Tax Cuts and Jobs Act on the Tax-Competitiveness of Multinational Corporations - Michael Overesch; Leon G. A. Reichert; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2023)
We exploit the 2017 US tax reform to learn about the tax-competitiveness of US multinational corporations (MNCs) relative to their international peers. Matching on the propensity score, we compare pairs of similar US and European firms listed on the S&P500 or StoxxEurope600 in a difference-in-differences setting. Our results suggest significantly lower effective tax rates of US MNCs compared to their European competitors after the US tax reform. Additional tests show (i) that US MNCs have gained substantially in what we call tax-competitiveness, (ii) that the reform effect is more pronounced for MNCs with a high share of domestic activity, and (iii) that the tax reform did not change the international tax-planning behavior of US MNCs. We provide evidence that US MNCs already successfully engaged in international tax planning prior to the reform, and this behavior is unchanged after the tax reform.
Keywords: H25; H26; K34; 330; effective tax rate; tax reform; tax-competitiveness; tax avoidance; pair matching; difference-in-differences analysis; profit shifting